2005
DOI: 10.2175/106143005x67449
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Modeling in Activated Sludge Systems: A Case Study

Abstract: A model of temperature dynamics was developed as part of a general model of activated‐sludge reactors. Transport of heat was described by the one‐dimensional, advection‐dispersion equation, with a source term based on a theoretical heat balance over the reactor. The model was compared to several reference models, including a tanks‐in‐series model and the dispersion model with heat components neglecting biochemical‐energy inputs and other activated‐sludge, heat‐balance terms. All the models were tested under st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…The effects of different hydrodynamic models (1-D ADE vs. tanks-in-series model) and the contribution of specific heat components on temperature predictions were evaluated. figure 2.14 Observed and predicted temperature changes from bioreactor inlet to bioreactor outlet (a) and contributions of the individual components to the overall heat balance for the bioreactor (b) at the Rock Creek WWTP, Hillsboro OR (USA) (Makinia et al 2005b). A simple uncertainty analysis revealed that the model predictions were not extremely sensitive (±0.1-0.2 o C) to changes (±10%) in the net heat flux.…”
Section: Historical Background Of Temperature Modelling In Activated mentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of different hydrodynamic models (1-D ADE vs. tanks-in-series model) and the contribution of specific heat components on temperature predictions were evaluated. figure 2.14 Observed and predicted temperature changes from bioreactor inlet to bioreactor outlet (a) and contributions of the individual components to the overall heat balance for the bioreactor (b) at the Rock Creek WWTP, Hillsboro OR (USA) (Makinia et al 2005b). A simple uncertainty analysis revealed that the model predictions were not extremely sensitive (±0.1-0.2 o C) to changes (±10%) in the net heat flux.…”
Section: Historical Background Of Temperature Modelling In Activated mentioning
confidence: 99%
“…The input can be taken as a direct measurement from a meteorological station (Makinia et al 2005b) or calculated. Short-wave (solar) radiation (Φ sr ), mechanical energy (Φ m ), and biochemical process energy (Φ bp ) are always positive, whereas long-wave (atmospheric) radiation (Φ ar ), surface convection (Φ c ), surface evaporation (Φ ev ), aeration (Φ a ), heat exchange through reactor walls (Φ w ) can be either positive or negative depending upon local conditions.…”
Section: Temperature Model Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing practical experience, continuously developed and improved activated sludge-based models have been utilized to quantify and to evaluate the process performance (Makinia and Wells, 1999;Makinia, 2010;Yetilmezsoy, 2010;Yetilmezsoy, 2016). In recent years, various mechanistic models have been introduced for the assessment of a number of activated sludge-based problems such as modeling of activated sludge thickening in secondary clarifiers (Giokas et al, 2002), modeling of the steady-state biofilm activated sludge reactor under substrate limiting conditions (Fouad and Bhargava, 2005a;Fouad and Bhargava, 2005b), modeling of temperature dynamics for activated sludge systems (Makinia et al, 2005), estimation of completely mixed activated sludge reactor volume (Yetilmezsoy, 2010), prediction of the reduction of biosolids production by ozonation of the return activated sludge (Isazadeh et al, 2014), and prediction of the waste sludge volumetric flow rate (Yetilmezsoy, 2016). Although many other studies (Nuhoglu et al, 2005;Mulas, 2006;Pamukoglu and Kargi, 2007;Szilveszter et al, 2010;Bagheri et al, 2015;Liu and Wang, 2015) have focused on different modeling methodologies in the operation of activated sludge-based treatment plants, however, to date, there are no sound papers in literature regarding the development of explicit mathematical formulations that can be directly used for the prediction of the present aeration-related parameters in the steady-state completely mixed activated sludge process without writing a set of theoretical statements.To the best of the author's knowledge, this work is the first study specifically aimed at investigating new and practical expressions for the direct estimation of aeration-related parameters as a function of the most common biological, hydraulic, and physical design variables used in the design.…”
Section: Introductionmentioning
confidence: 99%
“…While a similar approach has been used by Makinia et al (2005), this model proposes to use monthly yield estimates to approximate monthly biochemical heat factors based on specific organic substrates. As suggested by Argaman and Adams, the yield plays a significant role in the biochemical heat generation, and, thus, a significant component to the equilibrium temperature.…”
Section: Introductionmentioning
confidence: 99%